Technology Adoption: Evidence from an E-Government Cloud Service - Kriti Priya Gupta (Foresight and STI Governance, 2025)
This study investigates the effects of formal and informal external factors on citizens’ intention to use DigiLocker, which is a government-backed cloud storage service (CSS). It also examines how trust in government moderates these effects. This research framework is grounded in institutional theory. The proposed model was validated by quantitative analysis of primary data collected through a survey in Delhi, the national capital region (NCR) of India.The findings indicate that pressures can be divided into two categories — 1) formal (coercive pressure), and 2) informal (mimetic, and normative). Both significantly influence citizens’ attitudes, which in turn influence their intention to use DigiLocker. Moreover, coercive pressure has been found to be the strongest influencer of citizens’ attitudes. The moderating function of trust in the government has an ambiguous impact on different dimensions. That is, it is positive regarding the relationship between coercive pressures and citizens’ attitudes. At the same time it negatively moderates the relationships between mimetic and normative pressures and citizens’ attitudes. This study suggests that in order to effectively encourage the adoption of public CSSs, policymakers and service providers should consider the interplay of coercive, normative, and mimetic pressures along with trust.